STUDI POLA SPASIAL PERSEBARAN GAHARU (Aquilaria spp.) DAN KETERKAITANNYA DENGAN KONDISI HABITAT DI TAMAN NASIONAL KUTAI KALIMANTAN TIMUR - Pribadi, Didit Okta (Center for Plant Conservation Bogor Botanic Garden, Indonesian Institute of Sciences, 2009)
Agarwood is an important forest product due to its high economic value. However, the natural population of agarwood species has been decreasing rapidly because of over exploitation, therefore the international trade of the most important agarwood species (i.e. Aquilaria malaccensis) is restricted to just a small quota. This research was conducted in an attempt to provide basic information for the conservation of Aquilaria spp. by identifying the species spatial distribution and habitat characteristics and developing a linkage model between their abundance and habitat characteristics. Data were collected through a field survey at Kutai National Park in August 2006 with Aquilaria spp. as the target species. Data on the species localities were used to determine the species densities and the value of Distance Index of Dispersion. The ordinance levels between the target species and the surrounding other species were identified using a correspondence analysis, while the linkage model between the species abundance and habitat characteristics was established using an ordinal multinomial logit model. The results showed that Aquilaria spp. had a low density (0.01/ha) and were spatially distributed in a clump pattern. The abundance of Aquilaria species had a close association with soil texture, humidity and acidity, land elevation, air temperature and humidity, and light intensity. The abundance decreased with increasing the proportion of sandy clay loam content, soil humidity and acidity, land elevation, and light intensity. In contrast, the abundance increased with increasing sandy loam content, air temperature and air humidity. The existence of A. malaccensis was likely to associate with the existence of Goniothalamus sp., Macaranga sp., Vordia splendidissima, Lygopodium sp., and Stachyphrynium borneensis.